SISTEM PENUNJANG KEPUTUSAN PEMILIHAN PERUMAHAN DENGAN MENGGUNAKAN METODE AHP - SRI MARDIYATI; JULIANA JULIANA; DEWI DRIYANI (LPPM, 2016)
The aim of this study was to analyze what criteria- criteria that need housing in the election. Criteria - criteria are then compared and in the search order of priority. In addition to the criteria in the choice of housing is also in search of any alternative housing that matches the desired criteria. Using data from the respondents are of cooperative employees and lecturer at the University of Indraprasta then do analysis using Hirarcy Process Analytical methods using a software expert choice. This type of research is descriptive research that aims to solve existing problems based on variables obtained from the literature. These variables are used to analyze the respondents' housing will be selected. The analysis will be in the scoring through a questionnaire and processed using AHP with the aid of Expert Choice software. Through software and methods that will get the most superior priority criteria as decision support for selecting housing. The author can draw the conclusion that the method of AHP adalan exact method used for the process of selecting alternative perumahan.Dengan using AHP showed housing election by order of housing is housing De Marco, Cibinong Green View and Ambar Waringin Elok. Keywords: AHP, criteria, house.